Upaya Organization of American States (OAS) Dalam Melakukan Mediasi Terhadap Sengketa Perbatasan Antara Costa Rica dengan Nicaragua pada Tahun 2010 - Sucitri, Ni Ayu; Fasisaka, Idin; Kumala Dewi, Putu Ratih (DIKSHI (DISKUSI ILMIAH KOMUNITAS HUBUNGAN INTERNASIONAL), 2019)
ABSTRACT This study analyzed the mediation effort that done by the Organization of American States (OAS) in Costa Rica and Nicaragua border dispute 2010. OAS members country support peaceful dispute settlement.The San Juan river is the border between Costa Rica and Nicaragua which has been a source of conflict between the two countries since 1821. Although the status of the river and navigation rights between the countries has been regulated in agreement, but the border conflict between two countries occurred again in 2010. The conflict began with dredging activities along the river accompanied by a military invasion by Nicaragua on Costa Rica’s Island, Calero Island. In Response, Costa Rica asked OAS to mediate the conflict. OAS as a regional organization that houses the two countries then conducted mediation efforts to resolve the Costa Rica border dispute with Nicaragua 2010.   Keywords : OAS, Costa Rica, Nicaragua, Mediation